# |
ODE |
Mathematica |
Maple |
\[
{}2 x y^{\prime }-y = 2 x \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+x y = 10 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = 1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = -\frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}5 y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+7 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }+2 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-7 x y^{\prime }+15 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime \prime }-3 x y^{\prime \prime }+3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x y^{\prime }+5 y = 10
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}+2 y-3
\] |
✓ |
✓ |
|
\[
{}\left (y-1\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+6 y = 10
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = 4 y
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = 9-y^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+\sqrt {16-y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-2 y^{\prime }+4 y = 4 x -1
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right )+3 y \left (t \right ), y^{\prime }\left (t \right ) = 5 x \left (t \right )+3 y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right ) = 4 y \left (t \right )+{\mathrm e}^{t}, y^{\prime \prime }\left (t \right ) = 4 x \left (t \right )-{\mathrm e}^{t}]
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+4 y = 5 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = f \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = f \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-4 y^{\prime }-12 x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 5-y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 4+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }-20 y^{\prime \prime \prime }+158 y^{\prime \prime }-580 y^{\prime }+841 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }+20 x y^{\prime }-78 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{2}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {x y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = x
\] |
✓ |
✓ |
|
\[
{}\left (4-y^{2}\right ) y^{\prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (y^{3}+1\right ) y^{\prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (y-x \right ) y^{\prime } = x +y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-9}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-9}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-9}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sqrt {y^{2}-9}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 3 x
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 3 x
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = 3 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = x -2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }-3 y^{2} = 0
\] |
✗ |
✓ |
|
\[
{}y^{\prime }+2 y = 3 x -6
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 y-4
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = 18
\] |
✓ |
✓ |
|
\[
{}x y^{\prime \prime }-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y \left (-3+y\right )
\] |
✓ |
✓ |
|
\[
{}3 x y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 y-2\right ) y^{\prime } = 2 x -1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} = 4 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 6 \sqrt {y}+5 x^{3}
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+y = 2 \cos \left (x \right )-2 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \sec \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+y = \sec \left (\ln \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \sin \left (x \right ) = x
\] |
✓ |
✓ |
|